1998
DOI: 10.1007/s11661-998-0039-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environment on high-temperature hold time fatigue behavior of annealed 2.25 pct Cr 1 pct Mo steel

Abstract: Total strain control fatigue tests with a 120-second hold period at either peak compressive or tensile strain were conducted on annealed 2.25 pct Cr 1 pct Mo steel. Tests were performed at the total strain range of 1.0 pct at 500 ЊC or 600 ЊC in air, 1.3 Pa (10 Ϫ2 torr) or 1.3 ϫ 10 Ϫ3 Pa (10 Ϫ5 torr) vacuum. The nature of the hold and the environment affect fatigue life and surface crack patterns. A compressive hold is more deleterious than a tensile hold in high-temperature air, while the reverse is true in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 14 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…41 Now, 2.25Cr1MoV has greatly substituted the former, because its strength and resistance against hydrogen attack at elevated temperature are greatly improved after an addition of vanadium. 42 The low-cycle fatigue and creep-fatigue interaction of annealed ferrite 2.25Cr1Mo steel have been widely investigated by Brinkman et al, 43 Jaske, 44 Challenger and Vining, 45 and Hecht et al 46,47 since 1970s. They found that fatigue lives with compressed hold were shorter than with tensile hold for ferrite 2.25Cr1Mo steel, because compressed hold resulted in the more damaging tensile mean stress and circumferential cracks with cycling.…”
Section: Introductionmentioning
confidence: 99%
“…41 Now, 2.25Cr1MoV has greatly substituted the former, because its strength and resistance against hydrogen attack at elevated temperature are greatly improved after an addition of vanadium. 42 The low-cycle fatigue and creep-fatigue interaction of annealed ferrite 2.25Cr1Mo steel have been widely investigated by Brinkman et al, 43 Jaske, 44 Challenger and Vining, 45 and Hecht et al 46,47 since 1970s. They found that fatigue lives with compressed hold were shorter than with tensile hold for ferrite 2.25Cr1Mo steel, because compressed hold resulted in the more damaging tensile mean stress and circumferential cracks with cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the higher cyclic stress response is caused by the higher strain hardening, which is induced by the higher stain amplitude. Additionally, higher cyclic stress is also the reason that compressive holding time is negative for the lifetime, which has been achieved by Hecht et al 33 To better characterize the effect of strain amplitude and holding time, softening ratio is proposed. Geometry of the welded groove, complexity of the microstructure, and different crack propagation behaviour are accounted for the difference.…”
Section: Evolution Of Cyclic Stressmentioning
confidence: 99%
“…During compressive holding time, compressive creep strain is introduced, and as a result, material bears larger inelastic strain during tensile part of each cycle in comparison with the continuous LCF, accordingly, higher cyclic stress response is achieved for longer compressive holding time. Additionally, higher cyclic stress is also the reason that compressive holding time is negative for the lifetime, which has been achieved by Hecht et al 33 To better characterize the effect of strain amplitude and holding time, softening ratio is proposed. It is defined as the ratio of peak stress reduction in the middle lifetime to the peak stress in the first cycle.…”
Section: Evolution Of Cyclic Stressmentioning
confidence: 99%
“…Notched specimens were also tested. Hecht and Weertman (1998) reported the creep-fatigue data for 2.25Cr-1Mo steel at 500 and 600°C in air or in vacuum. Tests were carried out using hourglass-shaped specimens in uniaxial total strain control.…”
Section: Resolution Of Qualification Issues For Existing Structural Mmentioning
confidence: 99%